2022
DOI: 10.1002/adma.202201350
|View full text |Cite
|
Sign up to set email alerts
|

Large Room Temperature Anomalous Transverse Thermoelectric Effect in Kagome Antiferromagnet YMn6Sn6

Abstract: Kagome magnets possess several novel nontrivial topological features owing to the strong correlation between topology and magnetism that extends to their applications in the field of thermoelectricity. Conventional thermoelectric (TE) devices use the Seebeck effect to convert heat into electrical energy. In contrast, transverse thermoelectric devices based on the Nernst effect are attracting recent attention due to their unique transverse geometry, which uses a single material to eliminate the need for a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…We plotted and compared anomalous Nernst thermopower for FM-EuCd 2 As 2 with AFM-EuCd 2 As 2 , other reported ferromagnets and non-collinear As 2 in the present study and previously reported ferromagnet, antiferromagnet materials. [32,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] antiferromagnets (Figure 5). [32,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] FM-EuCd 2 As 2 exhibits large anomalous Nernst signal because the Weyl points lies close to Fermi level.…”
Section: Resultsmentioning
confidence: 99%
“…We plotted and compared anomalous Nernst thermopower for FM-EuCd 2 As 2 with AFM-EuCd 2 As 2 , other reported ferromagnets and non-collinear As 2 in the present study and previously reported ferromagnet, antiferromagnet materials. [32,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] antiferromagnets (Figure 5). [32,39,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] FM-EuCd 2 As 2 exhibits large anomalous Nernst signal because the Weyl points lies close to Fermi level.…”
Section: Resultsmentioning
confidence: 99%
“… working principle of thermoelectric conversion, i. e. the thermoelectric effect in longitudinal and transverse direction or the p‐n junction; [12,42–46] assumption of the geometrical model i. e. cuboid/ cylindrical; [47–50] dimension i. e. bulk or thin film; [51–55] flexibility i. e. flexible or rigid [56–61] …”
Section: Working Principle and Engineering Standpoint Of Thermoelectr...mentioning
confidence: 99%
“…working principle of thermoelectric conversion, i. e. the thermoelectric effect in longitudinal and transverse direction or the p‐n junction; [12,42–46] …”
Section: Working Principle and Engineering Standpoint Of Thermoelectr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ternary rare-earth tetrelides RE – T – Tt ( RE = rare-earth metal; T = transition metal; Tt = tetrel element) have been heavily studied due to their intriguing structure peculiarities, unconventional physical properties, and unprecedented bonding scenarios. Among them, intermetallics crystallizing with a disordered AlB 2 -type structure or with one of its ordered derivatives have attracted particular attention since the discovery of superconductivity with T c ∼ 39 K in MgB 2 , featuring similar honeycomb-like layers. Unfortunately, investigations of physical properties of these compounds were frequently not accompanied by accurate and in-depth structural analyses, which are indeed crucial to enable a correct interpretation of the observed phenomena.…”
Section: Introductionmentioning
confidence: 99%